Studying effect of Ncentive-Based Compensation on Managerial Performance - Ali Hamidizadeh; Jabar Babashahi, Maryam Kanafchian (مطالعات مدیریت بهبود و تحول, 2019)
This study examines the effect of incentive-based compensation schemes on managerial performance by clarifying the role of information asymmetry and organizational commitment as mediator. The research method in terms of purpose is among the descriptive and survey research data collection tool is questionnaire. The population of the study area was East Bank Saderat Gilan province. 183 people are selected with cluster way as sampling. Data is analyzed using structural equation modeling. The results suggest a positive effect of incentive - based compensation variable on managerial performance. The results also showed the positive effect of incentive - based compensation variable on managerial performance with considering the moderating role of organizational commitment. The results also reflect the negative impact of incentive- based compensation on information asymmetry as well as information asymmetry on the managerial performance.